2013
DOI: 10.1080/15017419.2013.859176
|View full text |Cite
|
Sign up to set email alerts
|

Client participation in medical rehabilitation for adults with severe disabilities

Abstract: The Social Insurance Institution (SII) of Finland arranges medical rehabilitation for people with severe disabilities. The rehabilitation process requires collaboration between the client and several organizations and professionals. The study aimed to find out what kind of experiences persons with disabilities had on their possibilities of participation in the planning and process of rehabilitation, and what factors were associated with the degree of their participation in the rehabilitation process. The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Several studies have identified paternalistic attitudes in many professional groups especially when making medical decisions (Lamont, Jeon, & Chiarella, 2013). A Finnish study (Järvikoski, Puumalainen, & Härkäpää, 2013) showed that although most clients with severe disabilities felt that they had been heard during their rehabilitation process, there were differences between client groups in their possibilities of being heard. According to the study, more attention should be paid to those clients who have, because of individual or system-based reasons, special difficulties in bringing forth their needs.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified paternalistic attitudes in many professional groups especially when making medical decisions (Lamont, Jeon, & Chiarella, 2013). A Finnish study (Järvikoski, Puumalainen, & Härkäpää, 2013) showed that although most clients with severe disabilities felt that they had been heard during their rehabilitation process, there were differences between client groups in their possibilities of being heard. According to the study, more attention should be paid to those clients who have, because of individual or system-based reasons, special difficulties in bringing forth their needs.…”
Section: Discussionmentioning
confidence: 99%
“…Participants, especially younger ones, exhibited higher participation levels in education, arranged daily activities, organisational activities and hobbies. Considering the goals of full participation by people with disabilities, the participants' participation was unevenly distributed, and nonparticipation was cumulative (see also Järvikoski et al, 2015).…”
Section: The Mixed-methods Contextmentioning
confidence: 99%
“…Haarni, 2006). According to recent Finnish research, the participation of people with severe disabilities especially needs greater attention (Järvikoski et al, 2015). In research based on interviews of people with disabilities, Hammel et al (2008) concluded that participation is individual but also entails various shared values, such as respect and dignity, as well as rights and responsibilities.…”
Section: Concepts Of Inclusion Participation and Disabilitymentioning
confidence: 99%
“…This literature broadly concentrates on three areas. First, especially in Scandinavian countries, emphasis rests on client participation in rehabilitation, sometimes referred to as 'user involvement' (Petersen et al 2012) or 'client-driven services' (Järvikovski, Puumalainen, and Härkäpää 2015;Virtanen et al 2011). In this context, children's participation in paediatric rehabilitation is discussed in particular (Bekken 2014a).…”
Section: Rehabilitation Walking and Normalitymentioning
confidence: 99%